Relevance of the values celebrated by the Shangani people in komba songs in the poest independence Zimbabwe - Masvayamwando, Kumbirai (Midlands State University, 2014)
This study is in the field of cultural studies and is on the values celebrated by the Shangani people in komba songs in the post-independence Zimbabwe. The study employs different data collection instruments like interviews and observation methods to gather much needed data in the compilation of this research. Qualitative research design is used in this study because it best suits in the field of social studies. The case study of Mwenezi has been used as the main point of data collection. Information gathered using the above mentioned data collection tools yielded the success of this research where data was analyzed and presented accordingly. Africana Womanism has been used as the cultural theory to guide the researcher to explore the position of men and women in the Shangani culture, how they continue to value certain cultural aspects whilst they face some challenges. The theory is important in this study because it values roles played by men and women in the African context in maintaining African traditional culture. It has been obtained in this research that the values which are celebrated in komba songs by the Shangani people are relevant in the post-independence period in Zimbabwe but are now dysfunctional due to some negative impacts on them which hinder their continuity in the modern society. The study has recognized some developments in the post-independence period which affect certain cultural values which are significant in cultural societies like the Shangani.